Culturological basis of the educational concept of designers at faculty of journalism (Herald of Journalism, 2018)
Article is devoted to the analysis of basic provisions and the principles of a culturological basis ofdomestic design. Authors of article outline a circle of problems of the educational concept of designerswithin faculty of journalism and also specifies potential opportunities of development of this specialization.Unfortunately, publishing practice abounds with sample design decisions, stereotypic developments.Copies of already successfully tested media projects are stamped by domestic designers. As aresult the Kazakhstan market of media design has deficiency of original products.Objective of this research: studying of fundamental methods, theories, the concepts making theesthetic nature of specialty “design”, culturological training of the professional designer within facultyof journalism.In article the concepts designating specifics of existence of “a gold kernel” of design activity, semanticfullness of all directions of training developing the art and design sphere are considered. SpecificsISSN 1563-0242 Herald of journalism. №1 (47). 2018 67Мухaмaдиевa Л.И., ДудиновaЕ.И.of specifically domestic model of design education and its creative annex to the media sphere come tolight. Authors come to a conclusion that the pedagogical concept of specialty is in dynamics, the numberof questions at the choice of priorities in the course of training isn’t solved: whether to consider specialtyof especially design, developing independently or directly included in system training of journalists;what foreign programs will fit most optimum into requirements of the domestic market, etc.Key words: culturological basis, media design, school of design, educational model, law of goldenratio, composition, symmetry, technological design.